Teachers Strategies in Implementing E-Modules in Biology Learning: A Systematic Literature Review - Wulandari, Sri; Kurniasih, Surti; Permana, Irvan; Ardianto, Didit (Universitas Negeri Semarang, 2025)
Education has an important role in improving the quality of each individual. One of the efforts teachers can make to create an active, innovative, and interactive classroom atmosphere is to provide learning materials that are interesting and relevant to technological developments. Electronic modules are an alternative to independent teaching materials according to student learning needs. This study aims to review the results of the Systematic Literature Review (SLR) related to teacher strategies in implementing E-Modules in biology learning. This study analyzed scientific articles from reputable sources such as Google Scholar, Springer Nature, ERIC, and Scopus, focusing on publications from 2020 to 2024. The review results show that teachers’ strategies in implementing e-modules are generally integrated with active and constructivist learning approaches that support the development of 21st-century skills. However, challenges like limited technological infrastructure, teachers’ readiness to design interactive media, and students’ adaptation to digital learning are still significant obstacles. Therefore, collaboration between educators, educational institutions, and the government is needed to overcome these obstacles by providing training, professional assistance, and adequate resources. It is hoped that the results of this study can be a reference for educators and researchers to develop more effective e-module implementation strategies in biology learning in the future.